Quantum Bio-inspired Invariant Object Recognition Model on System-on-a-Chip (SoC) - Loo Chu, Kiong; Teh Joo, Peng (2008)
This paper presents the first attempt of designing a physical quantum-like 'brain' for humanoid and experimentally proves a 2D invariant object recognition model inspired by the image processing along the human visual pathway: retina, lateral geniculate nucleus (LGN) and primary visual cortex (V1). It also describes storing the output of the model in quantum holographic memory (a hologram) and the method to reconstruct the visual representation. The work is implemented as system-on-a-chip in field-programmable gate array (FPGA).